Developing Next‐Generation Protein‐Based Vaccines Using High‐Affinity Glycan Ligand‐Decorated Glyconanoparticles. Issue 2 (18th November 2022) - Gao, Yanan; Wang, Wei; Yang, Yunru; Zhao, Qingyu; Yang, Chendong; Jia, Xiaoying; Liu, Yang; Zhou, Minmin; Zeng, Weihong; Huang, Xuefei; Chiu, Sandra; Jin, Tengchuan; et al.
Abstract: Major diseases, such as cancer and COVID‐19, are frightening global health problems, and sustained action is necessary to develop vaccines. Here, for the first time, ethoxy acetalated dextran nanoparticles (Ace‐Dex‐NPs) are functionalized with 9‐ N ‐(4H‐thieno[3, 2‐c]chromene‐2‐carbamoyl)‐Sia α 2−3Gal β 1−4GlcNAc ( TCC Sia‐LacNAc) targeting macrophages as a universal vaccine design platform. First, azide‐containing oxidized Ace‐Dex‐NPs are synthesized. After the NPs are conjugated with ovalbumin (OVA) and resiquimod (Rd), they are coupled to TCC Sia‐LacNAc‐DBCO to produce TCC Sia‐Ace‐Dex‐OVA‐Rd, which induce a potent, long‐lasting OVA‐specific cytotoxic T‐lymphocyte (CTL) response and high anti‐OVA IgG, providing mice with superior protection against tumors. Next, this strategy is exploited to develop vaccines against infection by severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2). The receptor‐binding domain (RBD) of the SARS‐CoV‐2 spike protein is the main target for neutralizing antibodies. The TCC Sia‐Ace‐Dex platform is preferentially used for designing an RBD‐based vaccine. Strikingly, the synthetic TCC Sia‐Ace‐Dex‐RBD‐Rd elicited potent RBD‐neutralizing antibodies against live SARS‐CoV‐2 infected Vero E6 cells. To develop a universal SARS‐CoV‐2 vaccine, the TCC Sia‐Ace‐Dex‐N‐Rd vaccine carrying SARS‐CoV‐2 nucleocapsid protein (N) is also prepared, which is highly conserved among SARS‐CoV‐2 and its variants of concern (VOCs), including Omicron (BA.1 to BA.5); this vaccine can trigger strong N‐specific CTL responses against target cells infected with SARS‐CoV‐2 and its VOCs. Abstract : By sequentially conjugating a protein antigen (PA), resiquimod (Rd), and 9‐ N ‐(4H‐thieno[3, 2‐c]chromene‐2‐carbamoyl)‐Sia α 2‐3Gal β 1‐4GlcNAc β Pro‐DBCO ( TCC Sia‐LacNAc‐DBCO) with partially oxidized azide‐displaying ethoxy acetalated dextran (Oxi‐Ace‐Dex‐Az) nanoparticles, a versatile TCC Sia‐Ace‐Dex‐PA‐Rd platform is developed. This novel platform has been successfully applied to develop next‐generation protein‐based vaccines against cancer, severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) and its variants of concern (VOCs).